Psychosocial Problems among Farmers in Agricultural Areas - Dewi Novi Maharani; Nadirotul Umami; Ulfi Yuliyani; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Alfid Tri Afandi (Health and Technology Journal (HTechJ), 2025)
Heavy work is one of the factors that can influence farmer stress. In addition, the high demand for labor can increase psychosocial disorders and psychological stress among farmers. This research aims to determine the management of psychosocial problems among Indonesian farmers. This research uses a literature review method which examines several academic articles related to the author's research. The data was obtained from the Google Scholar, PubMed, and Science Direct databases, and the publication years were 2020 to 2024. A systematic approach in the form of the PRISMA framework was used in selecting this literature review. In the English language literature search, the keywords "psychosocial" and "stress" and "farmer" were used. Then 10 relevant journals were selected based on inclusion and exclusion criteria. Agricultural nurses can educate farmers about psychosocial problems to reduce the psychosocial problems that occur. Farmers' psychosocial problems resulting from stress, depression, severe fatigue, and work exhaustion can be overcome not only with family social support but also with various types of self-management, such as focusing on problem-solving and controlling emotions.